1873 La. Acts 117 - (:unkn) unknown (My University, 1873)
An Act Conferring Certain Additional Powers and Privileges on the Metairie Cemetery Association, and to Punish Trespassers,§ 1: And any person who shall willfully destroy, mutilate, deface, injure or remove any tomb, monument, gravestone, or other structure placed therein, or shall willfully destroy, cut, break or remove any tree, shrub or plant within the limits of said cemetery, or shoot or discharge any gun or firearms within said limits, shall be deemed guilty of a misdemeanor, and shall upon conviction thereof, before any court or tribunal of competent jurisdiction
Keywords: DISCHARGE